Everyday discrimination and physical health: Exploring mental health processes. (October 2016) - Earnshaw, Valerie A; Rosenthal, Lisa; Carroll-Scott, Amy; Santilli, Alycia; Gilstad-Hayden, Kathryn; Ickovics, Jeannette R
Goals of this study were to examine the mental health processes whereby everyday discrimination is associated with physical health outcomes. Data are drawn from a community health survey conducted with 1299 US adults in a low-resource urban area. Frequency of everyday discrimination was associated with overall self-rated health, use of the emergency department, and one or more chronic diseases via stress and depressive symptoms operating in serial mediation. Associations were consistent across members of different racial/ethnic groups and were observed even after controlling for indicators of stressors associated with structural discrimination, including perceived neighborhood unsafety, food insecurity, and financial stress.